Cangfu Daotan decoction treats PCOS-IR through the IL6/JAK2/STAT3/FOXO4 signaling pathway - Ju, Wenhan; Zhang, Qianwen; Wang, Yue; Pan, Keying; Li, Yuan; Zhao, Shuai; Lian, Fang (Frontiers in Endocrinology, 2026)
ObjectiveThis study aimed to investigate the protective effects and underlying mechanisms of Cangfu Daotan Decoction (CDD) in both vivo and in vitro models of polycystic ovary syndrome with insulin resistance (PCOS-IR).Materials and methodsActive compounds in CDD were identified using UPLC-HRMS. Network pharmacology and molecular docking analyses were employed to predict key molecular targets. A nd a high-fat diet. In vitro, KGN cells were used to simulate granulosa cell dysfunction associated with PCOS-IR. The regulatory effects of CDD on the IL6/JAK2/STAT3/FOXO4 signaling pathway were further evaluated.ResultsFifteen active compounds in CDD were preliminarily identified. Ninety-four potential target genes related to the treatment of PCOS-IR were screened. Network pharmacology and molecular docking analyses indicated strong binding affinities between STAT3 and several active compounds of CDD. CDD improved ovarian function and reduced insulin resistance in PCOS model mice. In vitro, CDD also enhanced glucose intake in granulosa cells under PCOS-IR conditions. Both in vivo and in vitro experiments demonstrated that CDD significantly suppressed activation of the IL6/JAK2/STAT3/FOXO4 signaling pathway.ConclusionCDD may improve ovarian function and insulin resistance in PCOS-IR mice by modulating the IL6/JAK2/STAT3/FOXO4 signaling pathway.